Unlock the innovation potential of meaning of work: An empirical study of scientific and technological workers in China - Liang, Kexin; Lin, Sheng; Liu, Jinlan; Zhu, Yifan (Frontiers in Psychology, 2022)
Creativity and innovation have significantly increased in the past years. Amabile and Pratt were the leading proponents of creativity who integrated a dynamic componential model of creativity and innovation in organizations. The present study discusses the concept of innovative behavior within the scientific and technological environment based on the dynamic componential model of creativity and innovation and the Triadic Reciprocal Determinism Theory. The study investigates the mediating effect of achievement motivation and the moderating effect of the organizational innovative climate between the meaning of work and innovative behavior. Meaning of work has a positive impact on innovative behavior based on the structural equation modeling and the results of data collected from the survey of 4,666 scientific and technological workers in China. In addition, achievement motivation plays a partial intermediary role between the meaning of work and innovative behavior. However, innovation within organizational climate plays a negative regulatory role between achievement motivation and innovative behavior. The study finds some existing weaknesses through the Importance-Performance Map Analysis. Lastly, we examine the critical findings and present hypothetical suggestions.